Kulturowy wymiar designu – między estetyzacją a odpowiedzialnością - Głutkowska-Polniak, Alicja (Załącznik Kulturoznawczy, 2019)
When it comes to design, are aesthetic and ethical values oppositional to each other as they have been considered to be, or are they compatible and complementary? Design theorists and critics often distance themselves from aesthetic assumptions, focusing on ethical foundations and values based on duties towards another person (designer for the user) or responsibility. However, aesthetic values are clearly inscribed in the field of design. Firstly, because design is related to the appearance (aestheticization of reality) – form, harmony, and proportion between elements – but also to manipulation or simulation (aestheticization of design). In design as a cultural area, values interpenetrate and, at the same time, are ethical, social and aesthetic in their form and contexts; the aesthetic values especially permeate everything. They are not isolated in any separate order but rather they combine with other types of values.